Pattern of news media consumption and news discussion among youth: a test of agenda setting theory - Wok, Saodah; Tamam, Ezhar; Bolong, Jusang; Ahmad, Abdul Mua’ti @ Zamri (Faculty of Modern Languages and Communication, University of Putra, 2011)
Many studies on media consumption habits among youth have been conducted. Previous studies have reported that youth prefer news on online media compared to other forms of news media. This study tries to explore the pattern of news media consumption and interpersonal news discussions among youth. The specific objectives of the study are (1) to determine the level of perceived news media credibility, (2) to find out the level of news media consumption, (3) to find out the extent of interpersonal news discussions,(4) to analyze the relationship between perceived media credibility and news media consumption with interpersonal news discussions, and (5) to differentiate the effect of selected demographic characteristics on news media consumption and interpersonal news discussions. The survey research design method was used in the study. Data was collected using a set of self-administered questionnaires. A sample of 1363 was randomly selected using stratified random sampling. Malaysian youth aged 15-25 years old were gathered for the study. The data were analyzed using SPSS WIN 16.0 and descriptive and Inferential statistics were used. Findings of the study show that television (TV) is the most credible media followed by newspaper and the Internet. TV consumption is the highest among the youth. Findings also indicate that youth do discuss current news with family members and friends and that there are positive relationships between media credibility and news consumption which in turn influence family and friends news discussion. Within the sample investigated, male, Malay older youth are found to consume TV news the most. Older Indian youth depend on newspapers for news consumption and they discuss current national news with their family members and friends. In conclusion, the findings are in support of Agenda Setting Theory which states that news media consumption strongly influences interpersonal news discussion.